2016
DOI: 10.1016/j.joca.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The power and value of placebo and nocebo in painful osteoarthritis

Abstract: This paper reviews some recent advances in our understanding of the effects of sham or dummy interventions on pain and other symptoms in osteoarthritis (OA), and outlines two new approaches to the investigation of placebo and nocebo effects. We argue that the placebo effect provides us with a valuable way of investigating the nature of conditions like OA. For example, by examining which symptoms, biochemical markers or imaging features do or do not respond to placebo, we might learn more about the relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 70 publications
(94 reference statements)
1
29
0
6
Order By: Relevance
“…This is not surprising as a substantial placebo effect was previously reported in trials assessing drugs in OA 29 30. However, both active groups (CS and celecoxib) provided a significantly greater reduction in pain (VAS) and a better improvement in function (LI) than the placebo, after 6 months and 3 months, respectively.…”
Section: Discussionsupporting
confidence: 62%
“…This is not surprising as a substantial placebo effect was previously reported in trials assessing drugs in OA 29 30. However, both active groups (CS and celecoxib) provided a significantly greater reduction in pain (VAS) and a better improvement in function (LI) than the placebo, after 6 months and 3 months, respectively.…”
Section: Discussionsupporting
confidence: 62%
“…pain neuroscience education) commonly applied in clinical practice [ 35 37 ]. Third, CFs serve as additional tools for the interpretation of the clinical picture and guide clinicians in managing the complexity behind the patient’s musculoskeletal pain [ 38 ]. Taking into consideration CFs as active influencer of the therapeutic outcomes, can help to explain some unexpected outcomes and variability of symptoms experience [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…To elaborate, patients in a study with irritable bowel syndrome (although not a typical inflammatory disease, inflammatory processes have been linked to the pathophysiology of this disease) showed that when a physician adapted a more empathic communication style (the 'augmented' condition, focusing their communication style on warmth and confidence) relief rates increased from 44% to 62%, demonstrating the importance of a validating contextual cue in the generation of the placebo effect [37]. In contrast, invalidating contextual cues, for example when a health practitioner gives no or nonunderstanding feedback, may lead to high levels of arousal and can have detrimental consequences for the development of nocebo effects, again underlining the importance of the patient-doctor interaction [38]. Additionally, by openly administering placebo treatments and educating patients about the importance of treatment expectations (open-label studies), it was demonstrated that placebo's can still cause adequate relief [39].…”
Section: The Placebo Effect In Immune-related Conditionsmentioning
confidence: 98%